Increased Expression of miR-146a in Valvular Tissue From Patients With Aortic Valve Stenosis - Petrkova, Jana; Borucka, Jana; Kalab, Martin; Klevcova, Petra; Michalek, Jaroslav; Taborsky, Milos; Petrek, Martin (Frontiers in Cardiovascular Medicine, 2019)
miR-146a has been implicated in the regulation of the immune response as well as in inflammatory process of atherosclerosis. In the present study, we have investigated the expression of miR-146a and its targets, TLR4 a IRAK1, in aortic valve stenosis. A total of 58 patients with aortic stenosis (non- and atherosclerotic; tissue obtained during standard aortic valve replacement) were enrolled. The relative expression of mir-146a was higher in valvular tissue from patients with atherosclerosis compared to those without atherosclerosis (p=0.01). Number of the IRAK1 and TLR4 transcripts did not differ between the investigated groups. There was a trend towards elevation of miR-146a expression in context of inflammatory infiltrate observed in the valvular tissue from patients with atherosclerosis (p=0.06). In conclusion, in line with the acknowledged role of miR-146a in atherosclerotic inflammation, our data suggest it may be extended to the specific location of aortic valves in aortic stenosis.